2018
DOI: 10.1093/cid/ciy517
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Influenza and Pertussis Vaccination in Pregnancy in a Cohort of Australian Mother-Infant Pairs, 2012–2015: The FluMum Study

Abstract: Background. Inactivated influenza vaccine (IIV) and pertussis vaccination are recommended in pregnancy. Limited safety data exist for women who received IIV vaccine during the first trimester of pregnancy or received both vaccines in pregnancy. We assessed adverse birth outcomes between vaccinated and unvaccinated pregnancies. Methods. Among prospectively enrolled Australian "FluMum" participants (2012-2015), primary exposure was receipt and timing of IIV during pregnancy. Primary outcomes included preterm bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Data are lacking on the safety of vaccination in the first trimester of pregnancy, and on safety endpoints such as miscarriage, preterm births, stillbirths, LBW and SGA infants. One Australian study published in 2018 found no increased risk in preterm births, low birthweight or SGA infants in pregnant women who received a seasonal IIV compared to unvaccinated pregnant women, 39 however only 3% of this national cohort (N=8,827 mother-infant pairs) were Aboriginal women. Prior to 2015, analyses were largely limited to specific vaccines used during the influenza A(H1N1) pandemic, 40 and observational studies used in a meta-analysis 38 were non-Indigenous women living in well-resourced populations of North America and Europe.…”
Section: Discussionmentioning
confidence: 89%
“…Data are lacking on the safety of vaccination in the first trimester of pregnancy, and on safety endpoints such as miscarriage, preterm births, stillbirths, LBW and SGA infants. One Australian study published in 2018 found no increased risk in preterm births, low birthweight or SGA infants in pregnant women who received a seasonal IIV compared to unvaccinated pregnant women, 39 however only 3% of this national cohort (N=8,827 mother-infant pairs) were Aboriginal women. Prior to 2015, analyses were largely limited to specific vaccines used during the influenza A(H1N1) pandemic, 40 and observational studies used in a meta-analysis 38 were non-Indigenous women living in well-resourced populations of North America and Europe.…”
Section: Discussionmentioning
confidence: 89%
“…It is unclear whether uptake is so poor due to the vaccine not being offered to pregnant women, vaccine refusal or failure to record vaccination receipt. There is recent evidence to suggest that the introduction of the maternal pertussis vaccination program has been the impetus for driving up IIV uptake in pregnancy since its implementation in 2015 [42] although the data are lacking for NT Aboriginal women and sample sizes for Aboriginal women in other states were small or absent [40, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women are particularly susceptible to developing severe influenza illness and have an increased risk for hospital admission, although the mortality rate compared to non-pregnant women may not be increased [156][157][158]. Overall, it has been established that vaccinating pregnant women is safe, with no evidence demonstrating a link between immunization during pregnancy and adverse outcomes in offspring [159][160][161][162][163][164][165]. Infants born to mothers who were vaccinated against influenza may have a decreased rate of preterm birth, low birthweight, and stillborn birth, although establishing a causal relationship is challenging [160,[166][167][168][169][170][171].…”
Section: A Key Role For Maternal Vaccination In Protecting Young Infamentioning
confidence: 99%
“…Such data are valuable, however, a deeper understanding of additional factors that could have contributed to an adverse event is necessary in order to minimize the risk of drawing an invalid conclusion associating an adverse event with vaccination. Vaccinating pregnant women is generally regarded as safe [159][160][161][162][163][164][165]. However, some hesitancy over influenza vaccination is present in this population and the benefit of protecting both the mother and the fetus needs to be conveyed as outweighing the risk of potential side effects [223][224][225][226].…”
Section: Increasing Vaccination Rates For Influenzamentioning
confidence: 99%